Broadband complex permittivity measurements of dielectric substrates using a split-cylinder resonator - Janezic, M.D.; Kuester, E.F.; Jarvis, J.B. (2004 IEEE MTT-S International Microwave Symposium, 2004)
We discuss a theoretical model describing the split-cylinder resonator for non-destructive measurement of a dielectric substrate's relative permittivity and loss tangent. This improved model properly accounts for the fringing electric and magnetic fields in the dielectric substrate. Previously, the split-cylinder resonator has been used for single-frequency permittivity and loss tangent measurements using only the fundamental TE/sub 011/ resonant mode. By including high-order TE/sub 0np/ modes, we demonstrate how to measure the relative permittivity and loss tangent of dielectric substrates over an extended frequency range. We validated the new model by measuring the permittivity and loss tangent of fused-silica substrates from 10 to 50 GHz and comparing with results obtained with circular-cylindrical cavity, a dielectric-post resonator, and several split-post resonators.